Oral health promotion on social media: Perceptions of Malaysian young adults - Zaberi, Zarikh Hafizah Saqina; Mohd Nor, Nor Azlida; Kamarudin, Yasmin; Kherul Anuwar, Ainol Haniza; Hariyani, Ninuk (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Over the years, social media (SM) has become a powerful tool for communication and health promotion, enabling health professionals to connect with wider audiences in real time. However, there is a lack of qualitative data to understand end users’ perspectives on what is effective and what may require improvement. Purpose: This study aimed to explore preferences, reactions, and perceived impacts of oral health (OH) promotion on SM among Malaysian young adults. Methods: This qualitative study involved in-depth interviews with young adults aged 20–35 years. Purposive sampling was used to ensure diverse representation across several states in Malaysia. Twenty interviews were recorded and transcribed verbatim. Data were coded and analyzed thematically using Atlas.ti software. Three main themes—preferences, reactions, and perceived impacts—and seven sub-themes emerged from the analysis. Results: The young adults expressed positive views regarding OH promotion activities on SM. Most participants preferred visually appealing OH content, such as short videos and infographics, delivered in simple terms in the national language, and presented by health professionals. Although some participants identified as silent readers who did not actively engage with OH-related content, most believed that SM interventions had positively influenced their OH knowledge, attitudes, and behaviors. Conclusion: Most participants had positive perceptions of OH promotion through SM interventions, with some expressing clear content preferences. These findings may support the development of more effective OH promotion strategies in Malaysia that better align with user expectations.